Antipodal observations of global differential times of diffracted P and PKPAB within the D″ layer above Earth's core–mantle boundary. Issue 1 (1st April 2020) - Butler, Rhett; Tsuboi, Seiji
SUMMARY: Antipodal diffracted, compressional wave ( P diff ) data analysed diametrically opposite three large earthquakes have uniformly sampled 99% of the laterally heterogeneous zone above Earth's core–mantle boundary (D″ in seismic nomenclature). These antipodal data offer a fundamental gross Earth datum—a robust, global constraint on the average compressional velocity at the base of the mantle. We use for the first time the seismic phase PKPAB as a reference, which travels an identical mantle path as P diff, thereby cancelling common mantle heterogeneity. Differential traveltimes between P diff, PKPAB and PKIKP are measured, appropriately making allowance for the phase shifts acquired in propagation. We have independently confirmed the $π /4$ polar phase shift of P diff at the antipode. The global mean PKPAB − P diff time is 136.5 ± 0.6 s. The global mean apparent velocity (13.05 km s −1 ) and ray parameter (4.65 ± 0.01 s deg −1 ) are within the margin of error of prior P diff studies—which were dominated by Northern Hemisphere paths—indicating that complementary, southern hemisphere paths have a comparable, mean P diff apparent velocity. The seismic velocity constraints afforded by antipodal P diff and PKPAB suggest that the heterogeneous processes already observed in D″ may be broadly ascribed where D″ coverage has been lacking or poorly resolved.